Development of 11-Plex MOL-PCR Assay for the Rapid Screening of Samples for Shiga Toxin-Producing Escherichia coil - Woods, T. A.; Mendez, H. M.; Ortega, S.; Shi, Xiaorong; Marx, D.; Bai, Jianfa; Moxley, R. A.; Nagaraja, Tiruvoor G.; Graves, S. W.; Deshpande, A. (My University, 2016)
Strains of Shiga toxin-producing Escherichia coli (STEC) are a serious threat to the health, with approximately half of the STEC related food-borne illnesses attributable to contaminated beef. We developed an assay that was able to screen samples for several important STEC associated serogroups (O26, O45, O103, O104, O111, O121, O145, O157) and three major virulence factors (eae, stx(1), stx(2)) in a rapid and multiplexed format using the Multiplex oligonucleotide ligation-PCR (MOL-PCR) assay chemistry. This assay detected unique STEC DNA signatures and is meant to be used on samples from various sources related to beef production, providing a multiplex and high-throughput complement to the multiplex PCR assays currently in use. Multiplex oligonucleotide ligation-PCR (MOL-PCR) is a nucleic acid-based assay chemistry that relies on flow cytometry/image cytometry and multiplex microsphere arrays for the detection of nucleic acid-based signatures present in target agents. The STEC MOL-PCR assay provided greater than 90% analytical specificity across all sequence markers designed when tested against panels of DNA samples that represent different STEC serogroups and toxin gene profiles. This paper describes the development of the 11-plex assay and the results of its validation. This highly multiplexed, but more importantly dynamic and adaptable screening assay allows inclusion of additional signatures as they are identified in relation to public health. As the impact of STEC associated illness on public health is explored additional information on classification will be needed on single samples; thus, this assay can serve as the backbone for a complex screening system.
Citation: Woods, T. A., Mendez, H. M., Ortega, S., Shi, X. R., Marx, D., Bai, J. F., . . . Deshpande, A. (2016). Development of 11-Plex MOL-PCR Assay for the Rapid Screening of Samples for Shiga Toxin-Producing Escherichia coil. Frontiers in Cellular and Infection Microbiology, 6, 12. doi:10.3389/fcimb.2016.00092
Keywords: Stec; Mol-Pcr; Multiplex Pcr; Shiga Toxin; Ehec; Major Virulence Factors